The Study of Images of Nature Elements in the Poetry of Children and Adolescent Poets - Alireza Nabiloo; Maryam Baghi; Fatemeh Niazi (مطالعات زبانی و بلاغی)
The translation of Molana's books as a one of the greatest literary works of One of the main sources of imagery in the poetry of children and adolescents is the elements of nature. In this research, ten natural phenomena have been selected in the poems of 27 poets of different periods of time. The research method is library, analytical and statistical. First, the number of images used is extracted, then the contribution of each of the poets in creating the original images is determined. According to the data in Table one‚the most frequent new images are related to the rainbow (0.72), the sun and the moon (0.64) and the lowest images related to wind and breeze (0.43) and spring (0.35). In table two, the original images of each of the poets are collected. Jafar Ebrahimi 3/ 17‚ Asadullah Shabani 9/ 11, Qaisar Aminpour 8/ 8 are the most illustrative poets. Due to the nature, purpose and attention to the needs and minds of young children, poets who have written more for this group of poems, have less time to illustrate. Poets have used various imaginative techniques of sensory-abstract similes, eloquence, discernment and sensuality. In these illustrations, most of these elements have been used: human features, nature and products, objects, safe and place, animals, special terms.